Preparation of Magnesia Insulation Materials by Calcination of Walnut Shell Powder by Silica Sol Impregnation. (7th April 2021) - Kang, Chi; Li, Guohua; Han, Jishuo; Chen, Shujiang; Tian, Lin; Luo, Xudong; Yuan, Lin
Abstract : In this paper, magnesia porous aggregate was prepared by the foaming method with potassium oleate as the foaming agent. Secondly, the walnut shell powder was impregnated with the silica sol as the pore forming agent, and then, a new magnesia insulation material was prepared by 1300°C sintering. By changing the amount of the walnut shell powder added, the mechanical properties and thermal properties of the materials after sintering were studied. The results show that the sample with 10% walnut shell powder impregnated without the silica sol has a compression strength of 12 MPa. A sample with 10% walnut shell powder treated with the silica sol has a compression strength of 18 MPa. With the increase in the amount of the walnut shell powder added after impregnation, the bulk density, compression strength, and thermal conductivity of the sample all showed a decreasing trend, and the apparent porosity showed an increasing trend. When the additive amount is 20%, the bulk density of the sample is 1.029 g/cm 3, and the thermal conductivity is 0.382 W/m K (1050°C).